2014
DOI: 10.3109/0886022x.2014.900430
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of malondialdehyde, vitamin C and E in idiopathic nephrotic syndrome: a meta-analysis

Abstract: It is well documented that oxidative stress is involved in the pathogenesis of idiopathic nephrotic syndrome (INS). Malondialdehyde (MDA) is a measurement of lipid oxidation; vitamin C and E are important components of antioxidants. However, the association between MDA, vitamin C or E levels and INS remains elusive. A meta-analysis was performed to investigate the alteration of serum levels of MDA, vitamin C and E in INS compared with controls. Eight studies were included in our meta-analysis according to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…(2) Dietary factors are believed to play positive roles in reducing risk of cardiometabolic diseases, especially vitamin E supplementation. (3,4) In agreement, several observational studies (5)(6)(7)(8)(9)(10) suggested that vitamin E intake had a beneficial effect on protecting against cardiometabolic diseases. However, a large body of compelling literatures suggested that increased vitamin E intake was more likely to be associated with higher risk of cardiometabolic diseases.…”
supporting
confidence: 59%
“…(2) Dietary factors are believed to play positive roles in reducing risk of cardiometabolic diseases, especially vitamin E supplementation. (3,4) In agreement, several observational studies (5)(6)(7)(8)(9)(10) suggested that vitamin E intake had a beneficial effect on protecting against cardiometabolic diseases. However, a large body of compelling literatures suggested that increased vitamin E intake was more likely to be associated with higher risk of cardiometabolic diseases.…”
supporting
confidence: 59%
“…Phospholipids on cell membranes can be oxidized as oxidative stress damage, thus a stable lipid peroxide MDA was formed. MDA content reflects the degree of lipid peroxidation in the body as well as ROS attacking on cells (45). SOD is an important defense against free radical damage in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can contribute to the development and progression of NS by damaging the glomerular filtration barrier, promoting inflammation, altering lipid metabolism, impairing endothelial function and causing cellular damage (2,8). Several studies have shown that NS patients experience high levels of oxidative stress during the acute phase of the condition, and some studies have reported that oxidative stress markers remain elevated even after steroidinduced remission of the disease (7,9,10). Oxidative stress assessment entails evaluating both damaged stable molecules and antioxidant molecules, including enzymatic and non-enzymatic antioxidants.…”
Section: Introductionmentioning
confidence: 99%